Acute and posttraumatic stress disorders - Walters, Thomas; Insight Media (firm); CinemaHouse Films (New York, N.Y. : Distributed by Insight Media, 2002)
This video identifies the criteria for these disorders and the disabling symptoms that may arise with those affected by trauma. Examines how Acute Stress Disorder can evolve into a more chronic condition and the need for early intervention. Uses dramatic vignettes and interviews with professionals and educators in the field to discuss current treatment options and the challenges that these disorders present in home, vocational and clinical environments
Narrator : Shari Small
Keywords: Post-traumatic stress disorder; Stress (Psychology); Anxiety; Panic disorders; Agoraphobia; Social phobia; Obsessive-Compulsive Disorder; Tranquilizing drugs